Inventory Application Program on CV Y in Bandung - Dwi Febri Syawaludin (Politeknik Siber Cerdika Internasional, 2021)
Technology and Information are two things that cannot be separated today. This can be seen from the process to get information that can be obtained quickly, accurately, and accurately supported by increasingly sophisticated technological advances. This technological advancement makes many corporate agencies engaged in pawnshops use computer-based technology and networks to help their work because it is effective and efficient. Design of computer programs that the author made, it will soon be known what are the transactions without long in opening the documents. If the calculation process is applied computerized within the company, then the process will be very easy, automatically calculated and programmed so as not to waste a long time. Because the results of this programming process will be good in the office work cycle every day and very effective and efficient. The process of storage and input that is done dangan a programming that the author makes easy Pawnshop Prima Pawn in the process of data collection. In addition, citations also support the development of information technology